Influence of Organ Culture on the Characteristics of the Human Limbal Stem Cell Niche - Polisetti, Naresh; Martin, Gottfried; Ulrich, Eva; Glegola, Mateusz; Schlötzer-Schrehardt, Ursula; Schlunck, Günther; Reinhard, Thomas (International Journal of Molecular Sciences, 2023)
Organ culture storage techniques for corneoscleral limbal (CSL) tissue have improved the quality of corneas for transplantation and allow for longer storage times. Cultured limbal tissue has been used for stem cell transplantation to treat limbal stem cell deficiency (LSCD) as well as for research purposes to assess homeostasis mechanisms in the limbal stem cell niche. However, the effects of organ culture storage conditions on the quality of limbal niche components are less well described. Therefore, in this study, the morphological and immunohistochemical characteristics of organ-cultured limbal tissue are investigated and compared to fresh limbal tissues by means of light and electron microscopy. Organ-cultured limbal tissues showed signs of deterioration, such as edema, less pronounced basement membranes, and loss of the most superficial layers of the epithelium. In comparison to the fresh limbal epithelium, organ-cultured limbal epithelium showed signs of ongoing proliferative activity (more Ki-67+ cells) and exhibited an altered limbal epithelial phenotype with a loss of N-cadherin and desmoglein expression as well as a lack of precise staining patterns for cytokeratin ((CK)14, CK17/19, CK15). The analyzed extracellular matrix composition was mainly intact (collagen IV, fibronectin, laminin chains) except for Tenascin-C, whose expression was increased in organ-cultured limbal tissue. Nonetheless, the expression patterns of cell–matrix adhesion proteins varied in organ-cultured limbal tissue compared to fresh limbal tissue. A decrease in the number of melanocytes (Melan-A+ cells) and Langerhans cells (HLA-DR+, CD1a+, CD18+) was observed in the organ-cultured limbal tissue. The organ culture-induced alterations of the limbal epithelial stem cell niche might hamper its use in the treatment of LSCD as well as in research studies. In contrast, reduced numbers of donor-derived Langerhans cells seem associated with better clinical outcomes. However, there is a need to consider the preferential use of fresh CSL for limbal transplants and to look at ways of improving the limbal stem cell properties of stored CSL tissue.
CRIS-Team Scopus Importer:2023-12-22
Keywords: conjunctiva; cornea; extracellular matrix; human ocular surface; immunohistochemistry; limbal epithelial progenitor cells; limbal niche cells; limbal stem cells; melanocytes